Aplikasi Game 2D berbasis Andorid dengan Logika Fuzzy pada NPC (Non-Player Character): Android-based 2D Game Application with Fuzzy Logic on NPC (Non-Player Character) - Ibzani Ilham Shagianto; Giri Wahyu Wiriasto; Djul Fikri Budiman; Misbahuddin; Ni Made Seniari (JEITECH (JOURNAL OF ELECTRICAL ENGINEERING AND INFORMATION TECHNOLOGY), 2023)
Various games emerge with different types, platforms, qualities, and popularity. This is due to the integration of many tools with the Android Operating System. Therefore, the main objective of this research is to create a game in the form of an application with Artificial Intelligence for Non-Player Characters (NPC). The implementation of Fuzzy Logic on the NPC aims to enable the NPC to make Decision Making (DM) for dynamic movements, attacking the character played by the human player with the intention of inflicting damage through forward, backward, and attacking movements, gradually reducing the health point (HP) parameter until it is depleted, thus allowing the NPC to win the game. Similarly, the human player will also attack the NPC with forward, backward, jumping, and attacking movements. We named this mobile game "Battle Fence" and it can be played on the Android platform. Furthermore, fuzzy logic plays a role in several modes that we have prepared, such as the "rage" mode, where the NPC can automatically increase its movement speed to attack the human player when the NPC's HP-bar parameter is approaching depletion. Another mode we provide, also possessed by the NPC, is the "back-to-life" mode, where the NPC can revive after being defeated by the human player with an increased health point bar compared to before. The test results show an increase in the Attack-dmg parameter by 20 points, while the Max-Health parameter increased by 100 and 84 points. Based on these results, it can be concluded that the DM and the development of the HP parameter in the application work effectively